Circulating FH protects kidneys from tubular injury during systemic hemolysis - Merle,NS; Leon,J; Poillerat,V; Grunenwald,A; Boudhabhay,I; Knockaert,S; Robe-Rybkine,T; Torset,C; Pickering,MC; Chauvet,S; Fremeaux-Bacchi,V; Roumenina,LT (Frontiers in Immunology, 2020)
Intravascular hemolysis of any cause can induce acute kidney injury (AKI). Hemolysis-derived product heme activates the innate immune complement system and contributes to renal damage. Therefore, we explored the role of the master complement regulator Factor H (FH) in the kidney's resistance to hemolysis-mediated AKI. Acute systemic hemolysis was induced in mice lacking liver expression of FH (hepatoFH−/−, ~20% residual FH) and in WT controls, by phenylhydrazine injection. The impaired complement regulation in hepatoFH−/− mice resulted in a delayed but aggravated phenotype of hemolysis-related kidney injuries. Plasma urea as well as markers for tubular (NGAL, Kim-1) and vascular aggression peaked at day 1 in WT mice and normalized at day 2, while they increased more in hepatoFH−/− compared to the WT and still persisted at day 4. These were accompanied by exacerbated tubular dilatation and the appearance of tubular casts in the kidneys of hemolytic hepatoFH−/− mice. Complement activation in hemolytic mice occurred in the circulation and C3b/iC3b was deposited in glomeruli in both strains. Both genotypes presented with positive staining of FH in the glomeruli, but hepatoFH−/− mice had reduced staining in the tubular compartment. Despite the clear phenotype of tubular injury, no complement activation was detected in the tubulointerstitium of the phenylhydrazin-injected mice irrespective of the genotype. Nevertheless, phenylhydrazin triggered overexpression of C5aR1 in tubules, predominantly in hepatoFH−/− mice. Moreover, C5b-9 was deposited only in the glomeruli of the hemolytic hepatoFH−/− mice. Therefore, we hypothesize that C5a, generated in the glomeruli, could be filtered into the tubulointerstitium to activate C5aR1 expressed by tubular cells injured by hemolysis-derived products and will aggravate the tissue injury. Plasma-derived FH is critical for the tubular protection, since